Optimal Pricing of Electricity in Restructured Electricity Market - G.Umale, V.; S.B.Warkad, Dr.; Wadhankar, S.; S.Sakhare, H. (International Journal of Engineering and Technology, 2018)
An effective pricing scheme that to provide the useful information to generation, transmission section and customers. These transmission pricing depends on generator, load levels and transmission line constraints. Transmission line constraints result is variations in energy prices throughout the network. The proposed approach is based on AC-DC optimal power flow model with considering of losses. Resulting optimization problem is solved by linear programming approach. Locational Marginal Pricing methodology is used to determine the energy price for transacted power and to manage the network congestion and marginal losses. Variation of LMP values with transmission constraint conditions also studied. Simulation is carried out on IEEE 57 bus system, 400/765kV MSETCL system of Maharashtra transmission line for real data bus system and the results are presented.Â Â Â